Proposal of communicative activities to expand vocabulary in 4 th graders from "Ramón Pando Ferrer" Primary School - Anagua Yarari, Keyla (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2013)
The Cuban National System of Education is under processes of transformation aimed at the multilateral formation of students as a way of increasing and developing their cultural level. English is in the curriculum of Primary School and its goals are to get familiar with and sensitize girls and boys with the characteristics of the English language, but the results obtained are not yet the ones expected. This investigation presents a proposal of communicative activities to increase 4th grade students’ vocabulary in English from "Ramón Pando Ferrer" primary school. It consists of six communicative activities, two of them adapted from the current workbook to fit in the English program and 4 are created by the authoress. To achieve the objective of this research, it was necessary to employ several methods of investigation. From the theoretical level, the authoress used the analytic-synthetic, the inductive-deductive and the historic-logic. From the empirical level; the observation, pedagogical test, and analysis of the student’s notebooks, as well as the percent analysis from the mathematic level. The sample was selected intentionally out of a population of 20 students from fourth grade students from “Ramón Pando Ferrer” Primary School and it was due to the fact that it is the group where the authoress of this investigation does her practicum
Keywords: Educación Primaria; Inglés; Enseñanza